(untitled) (Islas, 2026)
Introduction: Mexico City hosts a large number of restaurants, which serve as key spaces for social interaction and leisure. This article evaluates cognitive accessibility within this sector and proposes a methodological approach based on easy-to-read language to improve it. Easy-to-read is a global strategy that enables texts to convey information in a clear and understandable way for individuals who require this support. When applied to the gastronomic sector, this strategy helps remove comprehension barriers and ensures universal accessibility. Methods: Phase 1: Selection of six restaurants in Mexico City. Phase 2: Description of the methodology for analyzing the cognitive accessibility of menus (qualitative approach), supported by standards and guiding frameworks. Phase 3: Specific recommendations based on results and guidelines. Results: The analyzed menus present significant cognitive barriers, including complex texts and poorly accessible design. None fully comply with the easy-to-read principles established in the UNE 153101 standard. The analysis has made it possible to generate specific recommendations for menu design, as well as a template. Conclusions: The study identified a gap between existing regulations on cognitive accessibility and their actual implementation in restaurants. The establishments analyzed lack readability criteria and easy-to-read principles. In response to this situation, a methodology based on the UNE 153101 standard and practical tools for accessible writing is proposed. The urgency of integrating the cognitive dimension into the gastronomic offer is highlighted as part of a broader commitment to inclusion.